Fungsi dan Muatan Nilai-Nilai Budaya dalam Basanan Using Banyuwangi - Syuhadak Syuhadak* (Universitas Muhammadiyah Jember, 2016)
Cultural society has its own ways and tradition to express ideas and thoughts which exists in a community. In Banyuwangi community it is called as Using Community named as basanan. As a part of Using Community in Banyuwangi, basanan has its functions and cultural values which reflect its society. The purpose of this study to describe those purposes and traditional values of basanan in Using community. Descriptive-qualitative method is applied in this article to gather the data. The techniques applied are participant observation, interviews and documentation. The data was analyzed based on Spradley (1997) ethnography model which comprises (1) domains analysis, (2) the taxonomic analysis, (3) componential analysis, and (4) ordered cultural themes analysis. The results of this study showed that thefunctions of basanan in the Using Banyuwangi community involved recommendation or advice, satire, humor, feelings, and praise; meanwhile the cultural values of basanan in Using Banyuwangi community involved religious, social, and personality values.Key words: Banyuwangi, basanan, functions, cultural values.